Discover bionics - Bethea, Nikole Brooks (Minneapolis : Lerner Publications, 2017)
"Discover how the science of bionics takes survival mechanisms from nature to create more efficient technology and save human lives. Simple language paired with descriptive images make this book perfect for reluctant readers."--
What is bionics? -- Restoring lost function -- Keeping us alive -- Cutting-edge bionics.
Includes bibliographical references (page 39) and index.
Ages 8-11.
Grades 4 to 6.
Keywords: Bionics -- Juvenile literature; Artificial organs -- Juvenile literature; Prosthesis -- Juvenile literature; Medical innovations -- Juvenile literature